Green endoscopy: practical implementation. Issue Volume 13:Issue e1(2022) (10th June 2022) - Donnelly, Leigh
Abstract : There is a necessity for endoscopy services as a speciality to lead the way in creating more sustainable departments. It is important we seek to explore and implement practical measures to ensure endoscopy services are working to meet our sustainability goals. The following article explores the practical implementation of measures which can be taken to make endoscopy greener.